Pelaku Supervisi Pendidikan Di Indonesia - Yanti Fatmariyanti; Agus Gunawan; Enung Nugraha (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Supervision in Education continues to be a concern for stakeholders. Moreover, with the implementation of the Merdeka curriculum, all regulations related to education have undergone changes or adjustments. This writing aims to examine the laws and regulations governing supervisors and the theories that support them. The method used in writing this research is a qualitative method using library research. The results showed that educational supervision according to the latest laws and regulations was carried out by heads of education units, school/madrasah committees, central government and regional governments.